2021
DOI: 10.21203/rs.3.rs-1054474/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of Prerelease Methadone on Mortality Among People with HIV and Opioid Use Disorder After Prison Release: Results from a Randomized and Participant Choice Open-Label Trial in Malaysia

Abstract: Introduction: Mortality is elevated after prison release and may be higher in people with HIV and opioid use disorder (OUD). Opioid agonist therapy (OAT) with methadone or buprenorphine reduces mortality in people with OUD and may confer benefits to people with OUD and HIV leaving prison. Survival benefits of OAT, however, have not been evaluated prospectively in people with OUD and HIV leaving prison. Methods:This study prospectively evaluated mortality after prison release and whether methadone initiated bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Characteristics of observational studies are presented in eAppendix 4 (eTables 7-15 in the Supplement). Cohorts ranged from 110 to 306 786 participants and included people from Europe (20 of 36 studies [58%]; 278 977 people), Australia (6 studies [17%]; 103 715 people), Asia (5 studies [14%]; 311 658 people), and North America (5 studies [14%]; 110 631 people). Seventeen studies (47%) concluded follow-up in 2010 or later.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Characteristics of observational studies are presented in eAppendix 4 (eTables 7-15 in the Supplement). Cohorts ranged from 110 to 306 786 participants and included people from Europe (20 of 36 studies [58%]; 278 977 people), Australia (6 studies [17%]; 103 715 people), Asia (5 studies [14%]; 311 658 people), and North America (5 studies [14%]; 110 631 people). Seventeen studies (47%) concluded follow-up in 2010 or later.…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen studies (44%) used OAT registry data. Mortality data during and after OAT were stratified by methadone treatment for 28 of 36 studies (78%) and by buprenorphine treatment for 8 of 36 studies (22%) . Type of OAT was unspecified in 6 of 36 studies (17%) …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations